Pancreatic steatosis in children. Part 2. Risk factors, diagnostic possibilitiess and therapy - Yu.M. Stepanov (Gastroenterologìa, 2017)
The article deals with the pancreatic steatosis in children — a pathological condition that is characterized by the accumulation of fat in the pancreas. The review presents data concerning risk factors, methods for diagnosis and treatment of pancreatic steatosis. The article demonstrates that the leading risk factors associated with pancreatic steatosis include obesity and metabolic syndrome. Diagnosis of pancreatic steatosis depends on non-invasive imaging techniques, such as transabdominal ultrasound, computed tomography, magnetic resonance imaging and endoscopic ultrasound. Therapy of pancreatic steatosis is based on lifestyle modification, therapy of dyslipidemia and carbohydrate metabolism disorders, correction of present exocrine insufficiency. To write a review, we used database Scopus, Web of Science, MedLine, PubMed, Google Scholar, CyberLeninka, RSCI with following keywords: “pancreatic steatosis”, “non-alcoholic fatty pancreas disease”, “children”.